Student Responses to Articulate Storyline 3 Learning Media with a STEM Approach on Parabolic Motion Material - Murniati, Miranda Evi; Alex , Harijanto; Maryani, Maryani (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2023)
Student responses to learning can be poor if students feel uninterested in the learning media. Therefore, innovations in interactive, technology-based learning media that are easy to understand and engaging are needed to improve student responses. This study aims to assess student responses after implementing Articulate Storyline 3-based learning media. The research uses a descriptive quantitative method with data collection techniques involving a response questionnaire with three indicators and a Likert scale. The study was conducted at SMAN 1 Rogojampi during the even semester of the 2022/2023 academic year. The average percentage of student responses was 86.6%, categorized as very good. The highest percentage was in the cognitive indicator at 91.2%, followed by the affective indicator at 86.8%, and the conative indicator at 81.7%. The average percentage across all indicators was 86.6%, with a very good category.